THE DEVELOPMENT OF INTERDISCIPLINARY COMPETENCIES IN PHYSICS CLASSES TAUGHT IN TECHNICAL UNIVERSITIES –AS A MEANS OF SHALING THE ABILITY OF STUDENTS TO THINK INDEPENDENTLY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes modern pedagogical technologies used in physics classes and their role in shaping interdisciplinary competencies. The possibilities of fostering creative thinking, independent work, and professional skills among students through the integration of project-based research, information and communication technologies (ICT), and practical experience are demonstrated.